Type specimens of amphibians in the National Museum of Natural History, Leiden, The Netherlands - Miracle, M. Eulàlia Gassó; van Den Hoek Ostende, Lars W.; Arntzen, Jan Willem (Zootaxa, 2007)
The amphibian type specimens held in the National Museum of Natural History in Leiden are listed. A total of 775 type specimens representing 143 taxon names were encountered. The list provides the original name, the original publication date, pagination and illustrations, current name, type locality and notes on the type status.